Green training for sustainable procurement? Insights from the Brazilian public sector - Aragão, Claudia Gomes [UNESP]; Jabbour, Charbel Jose Chiappetta [UNESP] (Emerald, 2017)
Purpose: Human resources practices, particularly regarding environmental training, play a key role in the dissemination of sustainable supply chain practices, especially sustainable procurement. Both environmental training and sustainable procurement can prompt environmental maturity (EM) among organizations. However, little is known about the relationship between environmental training and the adoption of sustainable procurement in public sector organizations of emerging economies, such as Brazil. In this context, the purpose of this paper is to investigate the relationship between environmental training and the adoption of sustainable procurement in three Brazilian public/state universities. Design/methodology/approach: This research is qualitative and includes an exploratory study based on in-depth interviews with experts from the procurement section of Brazilian public universities. A methodological framework is proposed to analyze the results. The main questions that guided this study were: is there a relationship between the environmental-training initiatives and the adoption of sustainable procurement? Does this relationship, whether positive or negative, improve the maturity of environmental sustainability? And what is the future outlook for this issue in the context of public universities in Brazil? Findings: According to the results’ analysis, the impact of sustainable procurement practices among the public organizations analyzed was almost void. The environmental training produced limited accomplishments, although respondents viewed it as a source of potential improvement, which indicates a co-evolution of sustainable procurement, environmental training and EM. In the cases analyzed, an alignment was identified among the levels of sustainable procurement and environmental training adoption. Research limitations/implications: It was identified that the lacks of training and support from senior management, environmental culture, great bureaucracy and economic factors were considered barriers and difficulties to implementing environmental procurement practices. These barriers deserve further study. Originality/value: There is a lack of research on the relationship between environmental training and the adoption of sustainable procurement in emerging economies and in public sector organizations.
Keywords: Green training; Sustainable human resource management; Sustainable procurement; Sustainable supply chain management